Magnetic Nanoparticles based on Natural Silica as a Methyl Ester Forming Acid Catalyst - Falah Azizah Elmaria; S. N. Aisyiyah Jenie (Research Center for Chemistry - LIPI, 2021)
Natural silica has advantages in various fields such as catalysts, because it is easily obtained and applied in the chemical reaction process. The synthesis of natural silica-based magnetic acid catalyst, MSNP/SO42- aims to obtain a large yield from the reaction process between oleic acid and methanol to form methyl ester. Natural silica obtained from geothermal waste was washed with distilled water, then sol gel method was applied at pH of 4-6 to obtain SiO2 nanoparticles. FeCl3 was added to achieve the magnetic properties, and the cetyl trimethyl ammonium bromide (CTAB) is varied in order to attain optimal mesoporous size. Brunauer emmet teller (BET) results showed optimum results from 1: 2 molarity ratio between silica and CTAB with a surface area of 520.94 m2/g. The acidic properties were obtained by immersion using H2SO4 0.5 M. The catalyst were tested for the acidic and magnetic properties using temperature programmed desorption ammonia (TPD-NH3) and vibrating sample magnetometer (VSM) characterization resulting intotal acidity of 0.2488 mmol/g and. softmagnetic type, respectively. The BET surface area of the sulfate modified into MSNP/SO42-, was decreased by 114.44 m2/g. Application of MSNP/SO42- as a catalyst for forming methyl esters obtained a percentage of 85.41% yield based on the gas chromatography mass spectrometry (GC- MS) results.